PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA DALAM PENERAPAN MODEL PEMBELAJARAN ARIAS (ASSURANCE, RELEVANCE, INTEREST, ASSESSMENT, DAN SATISFACTION) - Kiki Efendi (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2016)
This article describes the influence of teachers' pedagogical understanding of mathematical abilities of vocational students in the application of learning models ARIAS (Assurance, Relevance, Interest, Assessment, and Satisfaction). The method used in this study is an experiment with a model of "pre-test post-test one group design". The population in this study Â is the students of class X SMK Negeri 1 Karawang and the Samples are taken as one class. The research instruments consisted of the test the ability of understanding mathematical and questionnaire pedagogical competence of teachers. The findings of this study is based on a simple linear regression analysis showed that: there significant pedagogical competence of teachers to students' mathematical understanding capabilities in the application of learning models ARIAS (Assurance, Relevance, Interest, Assessment, and Satisfaction). Based on these conclusions, the teachers should always improve pedagogy for learning mathematics interested students so that the students' mathematics learning increases and may consider learning ARIAS (Assurance, Relevance, Interest, Assessment, and Satisfaction) can be used as an alternative learning in the classroom to improve the results of students' mathematics learning.Keywords: learning model ARIAS (Assurance, Relevance, Interest, Assessment, and Satisfaction), pedagogical competence of teachers, the ability of mathematical understanding